An Error Analysis on Using Present Continuous Tense - Nurcholis Pramudiana; Ika Chairiyani (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to analyze the students’ error in using present continuous tense. The specific objectives were to analyze the percentage of the students’ error and their causes. In analyzing data, the researcher collected the data from the test that must be filled in by the students, identified the students’ errors on their answer sheet, described the types of students’ errors, counted it and analyzed. This research used the descriptive qualitative as the research method, in which include counted on analyzed and present the result of study by described on concluding it. The subject of this research is eight B grade students of SMP N 3 Karawang Timur, amounting to 40 students. The finding showed that there are 375 items of error made by the students. It is found that 56 items or 14,9% errors are addition, 79 items or 21,07% errors are misformation, 55 items or 14,7% errors are misordering, and the most dominant error was error in omission with the frequency 185 items or 49,33%. The causes of error are based on the theory by John Norris (Carelessness, first language inference, and traslacion).